Study of {332}<113> twinning in a multilayered Ti-10Mo-xFe (x = 1–3) alloy by ECCI and EBSD. Issue 1 (1st December 2016) - Gutierrez-Urrutia, Ivan; Li, Cheng-Lin; Emura, Satoshi; Min, Xiaohua; Tsuchiya, Koichi
Abstract: We have investigated the propagation of {332}<113> twins in a multilayered Ti-10Mo-xFe (x = 1–3) alloy fabricated by multi-pass hot rolling. The material contains a macroscopic Fe-graded structure (about 130 μm width) between 1 and 3 wt% Fe in the direction perpendicular to rolling. We observe strong influence of the Fe-graded structure in the twin propagation behavior. The propagation of {332}<113> twins that are nucleated in Fe-lean regions (~1 wt% Fe) is interrupted in the grain interiors at a specific Fe content, namely, about 2 wt% Fe. We ascribe this effect to the role of Fe content in solid solution on the stress for twin propagation. The interruption of twins in the grain interiors results in the development of characteristic dislocation configurations such as highly dense dislocation walls (HDDWs) associated to strain localization phenomena. The nucleation and propagation of these dislocation configurations is ascribed to the underlying plastic accommodation mechanisms of the stress field at the twin tips. We find that the crystallographic alignment of HDDWs is determined by the stress field at the twin tips and the deformation texture. The excellent plastic accommodation at the interrupted twin tips allows attaining the good ductility of the present material (total elongation of 28%). Abstract :